(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Every year, millions of infants throughout the globe are not breathing during birth and requireinfant resuscitation. Only if the medical personnel in the delivery room is well-versed in infantresuscitation can they guarantee the safety and health of the newborns. The purpose of this study was toassess nurses’ knowledge in newborn resuscitation. A descriptive cross-sectional study was carried outto evaluate nurses’ knowledge of newborn resuscitation procedures. The selection of participants wascarried out in a random fashion, much like a census. The 86 nurses who worked in the maternity unit atthe Parsa District NGO were questioned using a semi-structured interview schedule, and theirperformance was rated based on observations. The findings showed that 93 of respondents hadinadequate knowledge (85 score) and 90.7 had inadequate skills (85 score) when it came toNewborn Resuscitation. Working experience, specifically in a maternity unit, and completion of infantresuscitation training both correlate with increased skill when it comes to resuscitating neonates(p=0.034, p=0.028, and p=0.001, respectively). Knowledge and ability scores on the same questionconcerning baby resuscitation were shown to have a strong correlation in this study (p0.0018). In thisStudy discuss effectiveness of hands-on training programme Association with pre-test knowledgescore and selected demographic variable regarding basic neonatal resuscitation among Nurses.